2015
DOI: 10.1016/j.hsag.2015.04.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lumbosacral manipulation on growing pains

Abstract: Background: Growing pains are a frequent clinical presentation that continues to puzzle practitioners, with very little conclusive evidence in any medical field, including chiropractic.Objective: The aim of this study was to determine whether lumbosacral manipulations have an effect on growing pain symptoms.Methods: Thirty participants with growing pains between the ages of 4 and 12 years were recruited. The participants were placed into two groups of 15 participants each. Group 1 received lumbosacral manipula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…However, companies are 'now situated within a constitutional framework, and so in considering the "best interests" it is imperative that directors give preference to the values of the Constitution and the Bill of Rights'. 148 In Bester v Wright 149 the High Court found that a director will breach fiduciary duties if they fail to comply with a legal rule, whether it be in terms of the Companies Act, or and other law. It may, therefore, be argued that directors may be found to have breached their fiduciary duties if, in the exercise of such duties, they act contrary to the Bill of Rights.…”
Section: Personal Liability For Directors Under the Constitutional Pa...mentioning
confidence: 99%
“…However, companies are 'now situated within a constitutional framework, and so in considering the "best interests" it is imperative that directors give preference to the values of the Constitution and the Bill of Rights'. 148 In Bester v Wright 149 the High Court found that a director will breach fiduciary duties if they fail to comply with a legal rule, whether it be in terms of the Companies Act, or and other law. It may, therefore, be argued that directors may be found to have breached their fiduciary duties if, in the exercise of such duties, they act contrary to the Bill of Rights.…”
Section: Personal Liability For Directors Under the Constitutional Pa...mentioning
confidence: 99%